Consequences of UV‐enhanced community respiration for plankton metabolic balance. (26th January 2014) - Agustí, Susana; Regaudie-de-Gioux, Aurore; Arrieta, Jesús M.; Duarte, Carlos M.
Abstract : The net community production (NCP) of plankton communities affects their role as sources or sinks of atmospheric CO2 . Most estimates of NCP have been made by enclosing communities in bottles, generally glass borosilicate, that remove ultraviolet (UV)B and part of UVA wavelengths. A series of experiments were conducted to test whether NCP values from communities incubated excluding UVB (+ part of UVA) radiation (i.e., in glass borosilicate) differ from those of communities receiving the full solar radiation spectrum (i.e., incubated with quartz bottles) and to explore the effect of UV radiation on the respiration rates and bacterial production in these communities. Plankton NCP tended to be 43% lower, on average, when the rates were measured under full solar radiation than when UVB (+ part of UVA) was removed. Dark respiration was significantly enhanced after exposure to the full solar spectrum for most communities, showing lower values when previously incubated in a light environment free of UVB (‒50%) or in the dark (‒62%). Bacterial production was inhibited by natural sunlight but increased, as observed for community respiration, when transferred to the dark. Communities previously exposed to full solar spectrum showed the greatest increase in bacterial production when allowed to recover in the dark. The net result of these responses were an increase in community respiration and decline in net community production over 24 h, indicating that UVB radiation plays a major role in the metabolic balance of the ocean's surface ecosystem.